Unmanaged Diabetes and Elevated Blood Glucose Are Poor Prognostic Factors in the Severity and Recovery Time in Predominantly Hispanic Hospitalized COVID-19 Patients - Bajpeyi, Sudip; Mossayebi, Ali; Kreit, Helen; Cherukuri, Sundar; Mandania, Roshni A.; Concha, Jeannie B.; Jung, Hyejin; Wagler, Amy; Gupte, Akshay; Deoker, Abhizith (Frontiers in Endocrinology, 2022)
Diabetes is considered to influence the severity and length of hospital stay (LOS) in COVID-19 patients. It is not known whether a lack of diabetes management may magnify the severity and LOS in COVID-19 patients with diabetes. The purpose of the study was to determine the impact of unmanaged diabetes and acute glycemia on severity and LOS among hospitalized COVID-19 patients. This retrospective study used medical records from patients admitted to the University Medical Center, El Paso, TX with COVID-19. Glycemic control was assessed by fasting blood glucose (acute) and HbA1c (chronic); COVID-19 severity was measured by quick sepsis-related organ failure assessment (qSOFA) and the LOS was determined by the number of days spent in the hospital. Diabetes management with medication was self-reported by patients. There was no significant difference in severity and LOS between patients with and without diabetes. However, patients with unmanaged diabetes showed significantly greater severity and LOS compared to patients who managed diabetes. Patients with an elevated fasting blood glucose level also had a greater COVID-19 severity and LOS. In conclusion, unmanaged diabetes and blood glucose showed worsened severity and prolonged hospitalization in COVID-19 patients. Diabetes management should be considered in the treatment of COVID-19 patients.